Measuring structural resilience of economies: Globalization or deglobalization? - Kiss, Tibor; Sebestyén, Tamás; Braun, Erik (PTE KTK Műhelytanulmányok, 2021)
The discussion about the role and effects of international trade has begun to intensify recently. On the one hand, we know that specialization and participation in the international division of labor results in more efficient production structures that bring welfare gains. On the other hand, the resulting strong interconnectedness of countries allows for the rapid spread of shocks and a more volatile and vulnerable system. Overall, neither full self-sufficiency nor an extremely globalized production structure seems to be sustainable nowadays. However, the responsiveness of countries to shocks might depend on the resilience of the countries. A system’s (economy’s) level of resilience derives from two structural properties: redundancy and efficiency. An efficient system has only a few mutual relationships, which indicates strong specialized trade flows and corresponds to the highly globalized production processes of a country. In contrast, a redundant system has many more similarly weak connections signaling a less specialized and embedded position of elements within the system, corresponding to a lower level of involvement within the international division of labor. While it is clear that extreme efficiency and extreme redundancy are not optimal arrangements, finding the optimal combination in between is challenging. Putting this framework of system resilience into international trade and production networks may indicate the optimal trade-off between self-sufficiency (more redundant systems) and specialization within international trade (more efficient systems). In this paper we use methods from Ecological Network Analysis (ENA) to capture the countries' structural resilience, building on sector level input-output data. The cross-country analysis shows that countries are heterogeneous in terms of resilience, and the structure of the countries has become more effective and globalized between 2000 and 2014. Using econometrics tools, we find a strong and significant association between redundancy/efficiency and the level of international trade, confirming the use of the complex system perspective in international trade. Finally, we also examine the countries' level of self-organization and the window of vitality in terms of resilience.